Manifestasi Klinis Apendisitis Akut pada Anak di Rumah Sakit Islam Banjarnegara - Niko Yuandi; Mirza Nuchalida; Agus Ujianto; Meta Safila; Suripto Riayani (Jurnal Health Sains, 2021)
Acute appendicitis is the commonest abdominal emergency. It is mainly a disease of teenagers affecting the most productive section of the population. So prolongation of morbidity due to negative laparotomy is unwanted and at the same time delay in diagnosis of acute appendicitis is apprehended. The present study was conducted on 35 morphological proved cases of acute appendicitis. Detailed clinical, morphological was studied. Abdominal pain was present in all patients and right iliac fossa was the usual site of abdominal pain. A significant number of cases reported a migration of pain to right iliac fossa from periumbilical region. Nausea and vomiting were other common symptoms. pyrexia is more prominent in advanced appendicitis cases. Other important clinical features were related with types of appendicitis. morphology is vital for surgeons to assess their clinical diagnosis, which in the long run will consolidate the base of their clinical experience and enrich the understanding of the appendicitis of the appendix as a whole and improve their clinical judgment.